‘Everyone has their reasons for curating the data they have decided to keep’: a thematic analysis of data hoarding as digital curation practice - Maemura, Emily; Wagner, Travis L. (Information Research an international electronic journal, 2025)
Introduction. This paper presents a preliminary analysis of the r/DataHoarder subreddit, an online community focused on social, legal, and technical practices related to digital curation. We contrast how they conceptualize their practices with the models, frameworks, and capabilities established for digital curation in more traditional memory institutions. Method. We use thematic analysis to analyse top posts (n=170) from the subreddit, to determine how members conceptualize, describe, and enact their data hoarding practices. Findings. Two key themes are identified: a focus on materiality of storage for hoarding, and use of the subreddit to promote calls-to-action. Each theme is further analysed, identifying underlying motivations such as nostalgia and vigilantism. Discussion. We briefly discuss the theoretical and practical implications of these findings in contrast with workflows like the DCC curation lifecycle, while also addressing limitations of this preliminary work, and outlining potential new research directions moving forward. Conclusions. We have found this analysis presents useful counterpoints to commonly referenced and standardised practices of memory institutions. We believe this will continue to be a fruitful area of study as we conduct future work on how r/DataHoarder and similar communities conceptualise, practice, and develop their own ethical framework toward sustained access of digital materials.